Современное состояние и перспективы развития рентгеновской вычислительной томографии; Дефектоскопия; № 4 - Чахлов С. В. Сергей Владимирович; Осипов С. П. Сергей Павлович; Темник А. К. Анатолий Константинович; Удод В. А. Виктор Анатольевич (2016, 2016)
Заглавие с экрана